Adolescent awareness and experience of the pubertal changes: A qualitative study from Rwanda - Kellen Muganwa; Oliva Bazirete; Marie Chantal Uwimana; Marie Grace Sandra Musabwasoni; Olive Tengera; Joy Bahumura; Hellen Nwanko Chinwe; Emmerence Uwingabire; Elyse Muteteri; Francoise Mujawamariya; Emmanuel Habyarimana; Eugenie Mukeshimana; et al. (PLoS ONE, 2025)
Introduction The transition from puberty to adolescence involves significant body changes that manifest differently across young children. It is essential that adolescents become aware of these changes so that they can easily navigate puberty’s physical, emotional, and interpersonal changes safely in terms of sexual and reproductive health. In Rwanda, there remains a gap in literature on adolescents’ awareness and experiences of pubertal changes among school going adolescents; particularly among those enrolled as day students. This research was undertaken to explore the awareness and understanding of puberty-related changes among school-aged adolescents, as well as their personal experiences of these changes. The findings aim to enhance the sexual education curriculum in Rwanda, with a particular emphasis on day students in rural regions who may be vulnerable to peer and societal pressures that can potentially expose them risky sexual behaviours. Methods A qualitative study was conducted with 120 school-going adolescent girls and boys. Participants were selected using a purposive sampling approach. Twelve focused group discussions were formed in six secondary schools from rural and urban 12-years basic education in the Eastern province of Rwanda. Deductive thematic analysis was used to analyse data using Dedoose software. Results The analysis yielded two main themes: i) what adolescents know about the changes occurring during puberty, encompassing physical, emotional, and behavioral transformations, as well as the social interactions linked to these changes and their perceptions regarding the factors that influence these changes, and ii) personal experiences pertaining to the changes associated with puberty. Most of the participants were aware of body changes that happen during puberty. While puberty marked an achievement of maturity for most of the participants, the onset of menarche for female adolescents was unique due to the embarrassment it caused them. Conclusion The study found that some young girls experience menarche unprepared and get inadequate support to initially navigate that change. Therefore, caregivers should proactively get educated on pubertal changes so that they provide appropriate support to children to navigate puberty safely.